2013
DOI: 10.1016/j.resinv.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration in regional health status after the acute phase of a great disaster: Respiratory physicians' experiences of the Great East Japan Earthquake

Abstract: The findings may result from poor shelter or dwelling conditions, as well as overpopulation and lack of basic resources. Adequate shelters, supply systems, and protection from infection, including vaccinations, are needed to prevent deteriorations in health status after the acute phase of a natural disaster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…The ToMMo is performing three health studies of the residents of areas affected by the Great East Japan Earthquake: a threegeneration cohort study, a community resident cohort of participants aged 20 or older, and a child health study. Previous studies have reported health issues among survivors of the Great East Japan Earthquake with careful attention to vulnerable persons such as the elderly, disabled, and patients with respiratory illness (Kobayashi et al 2013;Ohkouchi et al 2013). However, there has been little research documenting children's health after this disaster.…”
Section: Introductionmentioning
confidence: 99%
“…The ToMMo is performing three health studies of the residents of areas affected by the Great East Japan Earthquake: a threegeneration cohort study, a community resident cohort of participants aged 20 or older, and a child health study. Previous studies have reported health issues among survivors of the Great East Japan Earthquake with careful attention to vulnerable persons such as the elderly, disabled, and patients with respiratory illness (Kobayashi et al 2013;Ohkouchi et al 2013). However, there has been little research documenting children's health after this disaster.…”
Section: Introductionmentioning
confidence: 99%
“…As of 2016, 1.7 million internally displaced persons were living in camps and collective centres, including shelters (2). Studies have shown that poor shelter or dwelling conditions (such as overcrowding, lack of basic resources, and poor sanitation) may lead to deteriorations in health (3)(4)(5)(6). For example, in the aftermath of the Great East Japan Earthquake and tsunami in 2011, the prevalence of asthma, exacerbations of chronic obstructive pulmonary disease (COPD), and community-acquired pneumonia were two to three times greater compared to the previous year, with half of the community-acquired pneumonia cases originating in evacuation shelters (6).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that poor shelter or dwelling conditions (such as overcrowding, lack of basic resources, and poor sanitation) may lead to deteriorations in health (3)(4)(5)(6). For example, in the aftermath of the Great East Japan Earthquake and tsunami in 2011, the prevalence of asthma, exacerbations of chronic obstructive pulmonary disease (COPD), and community-acquired pneumonia were two to three times greater compared to the previous year, with half of the community-acquired pneumonia cases originating in evacuation shelters (6). Individuals with asthma may be more susceptible to compromised living conditions and stress leading to a higher risk of asthma exacerbations and other complications (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many of these people, shelter or dwelling conditions often affect their physical and mental health (8,9). These situations could be particularly difficult for chronic conditions such as asthma.…”
mentioning
confidence: 99%